Experimental Comparison Between Wire Mesh and Electrical Capacitance Tomography Sensors to Predict a Two-Phase Flow Behaviour and Patterns in Inclined Pipe - Hameed, Ali I.; Abdulkareem, Lokman A.; Mahmood, Raid A. (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Two-phase flow behaviour and its flow patterns have a significant effect in many applications in industry. Oil-gas is one of the two-phase flow types that have many applications in petroleum and power stations. An oil-gas two-phase flow behaviour and flow patterns have been investigated in an inclined pipe using two different tomography sensors: Wire Mesh sensor (WMS) and Electrical Capacitance Tomography (ECT). A special experimental facility was designed and built to operate the tow-phase flow application in the inclined pipe with the various angle of inclination. A set of experimental data were collected using operating conditions which covered a two-phase flow range of superficial velocity of gas (Usl) from 0.05 to 0.52 m/s and superficial velocity of liquid (Usg) from 0.05 to 4.7 m/s at atmospheric pressure and room temperature. Three inclined angles to change the pipe’s inclination 45, 60, and 80-degree were applied in the experiments. The Comparison between the Wire Mesh Sensor (WMS) and Electrical Capacitance Tomography (ECT) was completed experimentally. The results revealed that there is a good agreement between the two sensors, however; the WMS had a higher frequency which was calculated 1000 frames per second compared with the ECT which worked at 200 frames per second.